Theoretical study and application of 2-phenyl-1, 3, 4-thiadiazole derivatives with optical and inhibitory activity against SHP1. Issue 2 (15th December 2021) - Zhang, Chun; Sun, Yi-Tao; Gao, Li-Xin; Feng, Bo; Yan, Xue; Guo, Xue-Hui; Ren, Ai-Min; Zhou, Yu-Bo; Li, Jia; Wang, Wen-Long
Abstract : This work offered a fluorescent and activated molecule PT10 against SHP1 firstly, which achieved the integration of visualization and inhibitory activity against SHP1 in enzyme molecular level. Abstract : Src homology-2 domain-containing protein tyrosine phosphatase 1 (SHP1) is mainly restricted to hematopoietic and epithelial cells and widely accepted as a convergent node for oncogenic cell-signaling cascades. The development of efficient methods for rapidly tracing and inhibiting the SHP1 activity in complex biological systems is of considerable significance for advancing the integration of diagnosis and treatment of the related disease. With this aim, we designed and synthesized five 2-phenyl-1, 3, 4-thiadiazole derivatives (PT2, PT5, PT8, PT9 and PT10) here based on the reported SHP1 inhibitors (PT1, PT3, PT4, PT6 and PT7). The photophysical properties and inhibitory activities of these 2-phenyl-1, 3, 4-thiadiazole derivatives (PT1–PT10) against SHP1 were thoroughly studied from the theoretical simulation and experimental application aspects. The representative compound PT10 exhibited a larger quantum yield than the other molecules because of the smaller geometric relaxation and reorganization energy of the excited state, which was consistent with the results from the fluorescence experiments in organic solvents. In addition, PT10 showed a selective fluorescence response for SHP1 activity and low cytotoxicity in HeLa cells. Lastly, it indicated the potential application in two-photon cell fluorescence imaging in the future according to the calculated excellent two-photon absorption properties. In this contribution, firstly, we offered the fluorescent and activated molecule PT10 against SHP1, which achieved the integration of visualization and inhibitory activity of SHP1 preliminarily at the enzyme molecular level.